The Effect of Compensation and Work Motivation on Employee Performance at PT Bhakti Karya Distribusi Indonesia, Sawangan Depok - Dwiyanti, Fifi; Nurhayaty, Ety (The Future of Education Journal, 2026)
This study examines the effect of compensation and work motivation on employee performance at PT Bhakti Karya Distribusi Indonesia (Sawangan, Depok). The research is motivated by the need to improve human resource effectiveness in the distribution industry through appropriate compensation policies and motivational strategies. This study employs a quantitative approach with a causal research design. The sample consists of 40 respondents. Data were collected using questionnaires and analyzed using multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results indicate that, partially, both independent variables compensation and work motivation have a positive and significant effect on employee performance. Simultaneously, compensation and work motivation significantly influence employee performance, with a contribution of 94,3% (R² = 0.943), while the remaining 5,7% is influenced by other factors outside the model. The practical implications of this study suggest improving the compensation system and enhancing motivational programs to optimize employee performance in distribution companies.